2005
DOI: 10.1007/s00775-005-0022-4
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenases in Desulfovibrio vulgaris Hildenborough: structural and physiologic characterisation of the membrane-bound [NiFeSe] hydrogenase

Abstract: The genome of Desulfovibrio vulgaris Hildenborough (DvH) encodes for six hydrogenases (Hases), making it an interesting organism to study the role of these proteins in sulphate respiration. In this work we address the role of the [NiFeSe] Hase, found to be the major Hase associated with the cytoplasmic membrane. The purified enzyme displays interesting catalytic properties, such as a very high H(2) production activity, which is dependent on the presence of phospholipids or detergent, and resistance to oxygen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
120
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 83 publications
(124 citation statements)
references
References 73 publications
4
120
0
Order By: Relevance
“…The NiFeSe Hase from Desulfovibrio vulgaris Hildenborough was isolated and purified as reported previously 24, 25. F 1 F 0 ‐ATPase from E .…”
Section: Methodsmentioning
confidence: 99%
“…The NiFeSe Hase from Desulfovibrio vulgaris Hildenborough was isolated and purified as reported previously 24, 25. F 1 F 0 ‐ATPase from E .…”
Section: Methodsmentioning
confidence: 99%
“…In the present work the genes for the periplasmic hydrogenases (Valente et al 2006). Since the [NiFeSe] hydrogenase is much less sensitive to oxygen than the other periplasmic hydrogenases (Valente et al 2005), it makes sense that it should be up-regulated in these conditions.…”
Section: Genes Involved In Energy Metabolismmentioning
confidence: 99%
“…baculatum [20] , and Desulfovibrio vulgaris Hildenborough [21] , which are group 1 uptake Hases, and from the methanogens Methanococcus vannielii [22] and Methanococcus voltae [23] , which are group 3 cytoplasmic Hases. We performed a survey of [NiFeSe] Hase sequences currently present in databases (September 2010).…”
Section: Distributionmentioning
confidence: 99%
“…The presence of Sec was manually checked in doubtful cases, and it was found that some Hases annotated as being [NiFeSe] [25] . The enzyme from D. vulgaris Hildenborough has been shown to be a lipoprotein, and thus to associate to the membrane through a lipidic group at the N-terminus of the large subunit [21,26] . It has a truncated lipoprotein signal peptide, restricted to the lipobox, and was the first lipoprotein shown to be translocated through the Tat, rather than the Sec, pathway [26] .…”
Section: Distributionmentioning
confidence: 99%
See 1 more Smart Citation